Single-Stage Surgical Reconstruction of Posttraumatic Compound Complex Fronto-Basal Cranial Vault Fracture in a Resource-Limited Practice. Issue 5 (July 2016) - Adeleye, Amos Olufemi; Olusanya, Adeola A.
Abstract : Background: The extant literature on the surgical treatment of posttraumatic compound, complex frontal basal calvarial skull fracture suggests that this be a staged procedure. There are many socioeconomic constraints in low-resource regions of the world to the feasibility of this standard practice. Methods: A single-stage operative procedure for the surgical treatment of these fractures in a neurosurgery practice in Nigeria is here annotated. In addition, an observational outcome analysis of this surgical technique in a prospective consecutive cohort of patients over a 6-year period is presented. Results: Fourteen patients, all males, mean age 33.9 years (SD, 6.6) underwent this surgical procedure. Majority were late neurosurgical referrals, hence median time to surgery was 96 hours (range, 48–2160). Twelve patients (85.7%) had history of loss of consciousness, median duration of 34 hours; 7 (50%) had associated brain contusions; 6 (43%) significant pneumocephalus; and acute extradural and subdural haematoma in 4 and 2 patients respectively. The surgery was successful in all; 13 (93%) had normal outcome on the Glasgow outcome scale at hospital discharge; 12 have been followed up for 1 to 72 months, median 33. Seven of these were for 30 months or more. There was no patient of surgical site infection in the perioperative or the follow-up period to date. The aesthetic outcome was also acceptable. Conclusion: The pragmatic surgical technique herein annotated appears clinically and aesthetically effectual in the operative treatment of compound, complex frontal basal cranial vault fracture.